Bridging the Borders: English for students of Civil Engineering - Mulej, Sabina (University of Maribor Press, 2019)
Students of civil engineering are aware that the knowledge of English is absolutely necessary in the modern world. They want to communicate with people from all over the world and use literature in English, both at their study and work. Present materials want to lead students toward these goals and are meant for 30 lectures in one semester.